Chimonanthus nitens Oliv. leaves flavonoids alleviate hyperuricemia by regulating uric acid metabolism and intestinal homeostasis in mice - Wenya Meng; Lingli Chen; Kehui Ouyang; Suyun Lin; Yang Zhang; Jing He; Wenjun Wang (Food Science and Human Wellness)
This study aimed to evaluate the alleviating effect of Chimonanthus nitens Oliv. leaves flavonoids (CLF) on hyperuricemia induced by potassium oxonate in mice. The results showed that CLF lowered the serum levels of uric acid (UA), creatinine and blood urea nitrogen, downregulated hepatic mRNA expressions of xanthine oxidase (XO), phosphate ribose pyrophosphate synthetase (PRPS) and adenosine deaminase (ADA) in hyperuricemia mice. In addition, CLF repaired renal injury by significantly down-regulating mRNA and protein expressions of renal UA reabsorption-related proteins and up-regulating the mRNA and protein expressions of UA secretory-related proteins. Finally, CLF inhibited UA synthesis and promoted UA excretion to alleviate hyperuricemia. Besides, CLF supplementation repaired the intestinal barrier function as demonstrated by significant increased mRNA levels of intestinal zonula occludens-1 (ZO-1), Occludin, mucin 2 (MUC2) and mucin 4 (MUC4), as well as decreased mRNA levels of toll-like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88) in mice. Further research showed that CLF treatment restored intestinal homeostasis mediated by improving the composition of gut microbiota and elevating the abundance of beneficial bacteria like Lactobacillus, Alistipes, Prevotellaceae_UCG-001 and Parasutterella. Overall, our findings revealed a novel function of CLF as a promising therapeutic candidate for the treatment of hyperuricemia.